Human-centred Design Workshops in Collaborative Strategic Design Projects: An educational and professional comparison - Liem, André; Sanders, Elizabeth B.-N (Design and Technology Education: An International Journal, 2013)
It has been found that the implementation of Humancentred Design (HCD) methods in the Fuzzy Front-End is not likely to lead to diversification in educational product planning exercises, where time lines are short and executors lack experience. Companies, interested to collaborate with Master-level Industrial Design students on strategic design projects, should have realistic ambitions with respect to innovation and value creation. Moreover, diversification is not the only generic growth strategy to gain competitive advantage. Value can also be created from developing new products for existing markets, or creating new markets for existing products. On the contrary, companies who aim for diversification in their generic growth strategies, may not always end up with a complementary ‘high valued’ design outcome. From a learning perspective, the understanding of HCD methods created awareness among students and companies that respect and empathy for the end-user are important for enriching their design processes, and as such increasing the chances for diversification in subsequent projects with clients. This study also compares the implementation of Human-Centred Design (HCD) methods in a professional /collaborative and an educational/collaborative strategic design project.